A study to determine perceptions of relevance of company law to accountancy students. - Goh, Geraldine Shu Shien. (2008)
A study to determine the perceptions of relevance of company law to Accountancy students in their field of studies and careers. A survey was conducted with the Year 2s, 3s and graduates.